Institutionalization of the Rules in Russian Innovation Policy in the 2000s. On the Example of a Business Incubator in the Novosibirsk Region - Chernysh, Anna (Journal of Economic Sociology, 2018)
The article explores how the rules of state support policy for innovation development arose and were fixed in Russia in the 2000s. The author considers Russian business incubators as a new organizational form that emerged as a result of the institutionalization of those rules. She analyzes this process through the prism of new institutionalism ideas in organizational theory and economic sociology. The author examines the launch of the state technopark and business incubator in the Novosibirsk region on the empirical basis on 26 structured interviews with the main stakeholders of the business incubator. The analysis focuses on the role and resources of the institutional entrepreneurs in the process of emergence of the new organizational form. The article describes the context of the process itself, groups and actors who were involved in the dispute about the rules of the business incubator, results of communication between them, and the importance of social skills. The history of the business incubator development shows the following features of the institutionalization of the rules of state support policy for innovation development: institution building has a better chance of success if there are not only already existing informal rules and profile practices, but also a working negotiation process between relevant stakeholders in search of suitable motivations for reaching common goals. This fact translates the professional task into a political dimension. Request for innovation from the federal authorities gives sociopolitical legitimacy, which is necessary for effective negotiation.